2021
DOI: 10.3390/su132212383
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Analytics from a Wastewater Treatment Plant

Abstract: Wastewater treatment plants (WWTPs) use considerable workforces and resources to meet the regulatory limits without mistakes. The advancement of information technology allowed for collecting large amounts of data from various sources using sophisticated sensors. Due to the lack of specialized tools and knowledge, operators and engineers cannot effectively extract meaningful and valuable information from large datasets. Unfortunately, the data are often stored digitally and then underutilized. Various data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Using big data, companies provide opportunities for employees to grow and develop through learning, improving performance, and predicting company growth (Hotaling & Spinrad, 2021). For example, Google uses people analytics to invest in their infrastructure better, answer critical questions that matter to the business, and as an essential component in building business partnerships (Wongburi & Park, 2021). The analytical capabilities possessed by Big Data can help identify human resources who have the potential to grow and develop rapidly so that they are entitled to further training so they can get a high career path (Jain, 2018).…”
Section: Employee Developmentmentioning
confidence: 99%
“…Using big data, companies provide opportunities for employees to grow and develop through learning, improving performance, and predicting company growth (Hotaling & Spinrad, 2021). For example, Google uses people analytics to invest in their infrastructure better, answer critical questions that matter to the business, and as an essential component in building business partnerships (Wongburi & Park, 2021). The analytical capabilities possessed by Big Data can help identify human resources who have the potential to grow and develop rapidly so that they are entitled to further training so they can get a high career path (Jain, 2018).…”
Section: Employee Developmentmentioning
confidence: 99%
“…Additionally, combining multiple models generally reduces errors compared to a single model, and the process of averaging or following the majority opinion mitigates extreme predictions, providing more stable results [16]. The governing equation for the weighted ensemble models is represented by Equation (1), where n represents the number of regressors in the ensemble, wi is the weight assigned to the i-th regressor, and yi(x) is the prediction made by the i-th regressor for the input x.…”
Section: Ensemble Modelmentioning
confidence: 99%
“…In recent years, there has been a remarkable surge in the volume of data generated and stored within wastewater treatment plants (WWTPs) since 2010, leading to an exponential increase. Notably, it has been observed that 90% of global data have been generated within the past two years alone, signifying the onset of the big data era [1].…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by prior research titled "Big Data Analytics from a Wastewater Treatment Plant", the significance of big data analytics in constructing a wastewater treatment plant model is noteworthy. The phases of big data analytics encompass data collection, data comprehension, data preprocessing, and data mining [21]. The details of big data analytics are as follows:…”
Section: Big Data Analyticsmentioning
confidence: 99%